Low-loss high entropy relaxor-like ferroelectrics with A-site disorder. Issue 4 (April 2021) - Xiong, Wei; Zhang, Hangfeng; Cao, Shuyao; Gao, Feng; Svec, Peter; Dusza, Jan; Reece, Michael J; Yan, Haixue
Abstract: Relaxor ferroelectric ceramics are good candidates for capacitor, sensor and actuator applications because of their high dielectric permittivity, high piezoelectric constant and high value of field induced strain, respectively. However, their dielectric loss is usually relatively high, which is a problem for actual applications. The introduction of the high entropy concept opens up the possibility of developing new multi-element relaxor-like ferroelectric materials with short-range ordered polar structures having short relaxation times to decrease their loss. Here we present a new high entropy A-site disordered perovskite (Pb0.25 Ba0.25 Sr0.25 Ca0.25 )TiO3 relaxor-like ferroelectric. Moreover, the ceramic has low loss (<0.015) from room temperature to 125 °C. The relaxor-like nature of the material is proved by dielectric and ferroelectric measurements. This work demonstrates the great potential of high entropy perovskites as relaxor-like ferroelectrics with a wide compositional window for tuning their properties for different applications.